Impact analysis of scaled truck model - Goh, Jia Yi (Nanyang Technological University, 2020)
In today’s world, anti-ram bollard system is crucial to safeguard the building from vehicle borne threat. thus, many experiments are conducted to study the impact analysis between the infrastructures or anti-ram bollard system, and the vehicles. However, it is expensive to conduct a real-time full-scale impact testing of such systems and not many design parameters can be tested. Thus, a computational analysis can be used to simulate the physical testing and evaluate the dynamic impact between infrastructure and the vehicle. This study aims to create a finite element model of an equivalent truck according to Ford F800 truck model and simulate the impact process between a medium or heavy truck and a reinforced-concrete column. The F800 truck model is represented by the equivalent truck constructed by mild steel column and blocks. To ensure the finite element model of the simplified truck is equivalent to the F800 truck model, reaction time history, internal energy time history and the deformation time history of the reinforced concrete column were analysed. The finite element model are built by the software called ABAQUS, according to the provided information from the experiment.